2020
DOI: 10.5194/acp-2020-188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constraining Ammonia Emissions in Vehicle Plumes Utilizing Nitrogen Stable Isotopes

Abstract: Abstract. Vehicle emissions have been identified as an important urban source of ammonia (NH3). However, there are large uncertainties regarding the contribution of vehicle emissions to urban NH3 budgets, as well as its role in spatiotemporal fine particulate matter (PM2.5) formation and nitrogen (N) deposition patterns. The N stable isotopic composition (δ15N) may be a useful observational constraint to track NH3 emission sources and chemical processing, but previously reported vehicle δ15N(NH3) emission sign… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…It should be noticed that sampling methods (active and passive samplers) also play a considerable role in the measured values of δ 15 N-NH 3 . 47 Walters et al 26 and Pan et al. 47 confirmed a low bias of passive samplers in δ 15 N-NH 3 observations compared to active samplers due to the isotopic effects of gas diffusion, while no significant differences were found between different passive samplers.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…It should be noticed that sampling methods (active and passive samplers) also play a considerable role in the measured values of δ 15 N-NH 3 . 47 Walters et al 26 and Pan et al. 47 confirmed a low bias of passive samplers in δ 15 N-NH 3 observations compared to active samplers due to the isotopic effects of gas diffusion, while no significant differences were found between different passive samplers.…”
Section: Resultsmentioning
confidence: 86%
“…However, particulate NH 4 + concentrations were not measured at the four on-road sites. For site 3 (tunnel interior), the f value was set at 0.044 on the basis of Walter et al, 26 who reported f was extremely low in the tunnel. For the other three on-road sites (sites 1, 2, and 4), we performed a sensitivity analysis in which we modeled f values ranging from 0.0 to 1.0 to estimate the expected δ 15 N-NH x .…”
Section: Methodsmentioning
confidence: 99%
“…Data availability. Data presented in this article are available on the Brown Digital Repository at https://doi.org/10.26300/q3h4-7s93 (Walters, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…23 However, the converters often over-reduce to NH3 which has contributed to a high rise in the nitrogen budget, instead of a decline. 24,25 Ammonia formation through this method also increases particle nucleation by several orders of magnitude. 26 Reduction of NOx emissions from both two-and three-way catalytic converters in vehicles have been shown to increase NHx (= NH3 + NH4 + ) emissions by approximately 15% in the atmosphere.…”
Section: Introductionmentioning
confidence: 98%
“…26 Reduction of NOx emissions from both two-and three-way catalytic converters in vehicles have been shown to increase NHx (= NH3 + NH4 + ) emissions by approximately 15% in the atmosphere. 27,28 Using Stable isotopes of Nitrogen ( 15 N, 14 N) as a tool to trace original sources of nitrogen pollutants through ratios 15 N/ 14 N sample compared directly to the international isotopic standard for nitrogen (atmospheric air) gives a number in a unit of per mil (‰) (δ 15 24,29,30,31,32,33,34,35 The partitioning of NHx between the gas, solid, and aqueous phases is driven by thermodynamic equilibrium that depends on the relative humidity, temperature, and particle chemical composition, making the separation of each phase(speciation) difficult. 36 Isotopic analysis for source tracing has shown great promise in terms of requisite time resolution, quantitative collections of concentration and no fractionation upon collection for collection of NHx(g) and pNH4 + with a reproducibility of ≤1.5‰ for application in multiple field environments.…”
Section: Introductionmentioning
confidence: 99%